Studi Tematik Ayat-Ayat Maḥabbah Perspektif al-Sha’rāwī dalam Tafsīr al- Sha’rāwī - Muiz, Abdul; Samdani, Dani (Institut Agama Islam Negeri Kediri, 2024)
This paper attempted to examine the nature of maḥabbah to Allah and His Messenger from the perspective of al-Sha’rāwī. There are two essential things to be studied in depth through one figure in this paper, including how the position of maḥabbah in the Qur'an and how Sheikh Muhammad Mutawallī Al-Sha'rāwī reveals the nature of maḥabbah in his tafsir, Tafsīr al-Sha'rāwī. The study includes thematic research on the verses of the Qur'an based on the interpretation of the character in his tafsir work. This research consists of a literature study that makes Tafsīr al-Sha'rāwī a primary source and literature related to the research topic as a secondary source. The data obtained is then analysed descriptively and analytically. The results reveal that al-Sha'rāwī places the position of maḥabbah in the Qur'an to be the highest level above all because love for Allah, namely maḥabbatullah, can be used as a reminder to doing good deeds and being able to leave bad things and can increase a servant's piety to Him. Al-Sha'rāwī, in revealing the essence of maḥabbah in his tafsir, provides an illustration in which a believer must always be connected to Allah Most High and put his trust in Him alone because a believer knows that putting trust in Allah means that the limbs work and the heart trusts.